Penerapan Teori Konsumen dalam Menganalisis Pola Konsumsi Masyarakat Modern - Pratiwi Musa, Kartika Septiary (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study aims to analyze the theories that explain consumer behavior and the factors that influence it in  the context of modern economics and marketing. The background of this research departs from the  importance of understanding how individuals make decisions in choosing and buying goods or services in  the midst of rapid social changes and digital technology. This study uses a library research method by  examining various scientific sources, books, and national and international journals published in the last  ten years (2015–2025). The results of the study show that consumer behavior is a multidimensional  phenomenon that involves the interaction between economic, psychological, social, cultural, and  technological aspects. Theoretically, consumer behavior is explained through cardinal utility theory,  ordinal utility theory, and inference curve theory, which describe how consumers seek to maximize  satisfaction with resource limitations. In addition, consumer behavior is influenced by internal factors such  as motivation, perception, attitude, and lifestyle, as well as external factors such as culture, social groups,  family, and economic conditions. The findings of this study confirm that consumer behavior in the digital  age is not only driven by economic rationality, but also by symbolic value, emotions, and awareness of  sustainability. This research is still conceptual, so further empirical studies are needed to test the  application of consumer behavior theory in different industry contexts. The results of this study are expected  to contribute to the development of management and marketing science, as well as become the basis for  companies to design adaptive, ethical, and sustainable marketing strategies.